Plasma Antimicrobial Peptide LL-37 Level Is Inversely Associated with HDL Cholesterol Level in Patients with Type 2 Diabetes Mellitus - Shu Meguro (International Journal of Endocrinology, 2014)
Introduction. Relation between atherosclerosis and innate immunity has attracted attention. As the antimicrobial peptide, LL-37, could have an important role in atherosclerosis, we supposed that there could be a meaningful association of plasma LL-37 level with risk factors for cardiovascular disease in subjects with type 2 diabetes mellitus. Materials and Methods. We evaluated plasma LL-37 level and other clinical markers in Japanese subjects with type 2 diabetes mellitus (n=133, 115 men and 18 women; age 64.7±11.5 years; HbA1c 8.1±1.6%). Plasma level of LL-37 was measured by ELISA. Results. Mean plasma LL-37 level was 71.2±22.3 ng/mL. Plasma LL-37 level showed significant correlations with HDL cholesterol (r=−0.450, P<0.01), triglyceride (r=0.445, P<0.01), and high sensitive C-reactive protein (r=0.316, P<0.01) but no significant correlation with age, body mass index, HbA1c, estimated glomerular filtration rate, 25-hydroxyvitamin D, or vitamin D binding protein. Multiple linear regression analysis showed significant correlations of plasma LL-37 level with HDL cholesterol (β=−0.411, P<0.01) and high sensitive C-reactive protein (β=0.193, P<0.05). Conclusion. Plasma LL-37 level was positively correlated with inflammatory markers and negatively correlated with HDL cholesterol in patients with type 2 diabetes mellitus.